2015
DOI: 10.1111/1556-4029.12794
|View full text |Cite
|
Sign up to set email alerts
|

The Erratic Behavior of Lesions in Burnt Bone

Abstract: This study analyses depressed fractures (by blunt force trauma) and circular full-thickness injuries (drill injuries and gunshot wounds) in charred bones. Fifty bovine ribs (total 104 lesions) were divided into three groups. The first group consisted in 20 depressed hammer-produced fractures; in the second one, 60 round drill-holes were produced (30 circular, 30 semicircular); in the third group, 12 fleshed and 12 skeletonized ribs were hit by 9-mm bullets. Each specimen was carbonized in an electric oven up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…The results have shown that signatures associated with sharp and blunt force trauma were not entirely masked by heat exposure and that there is potential for future standardization of fracture analysis in burnt bone given further experimentation of this nature. In the literature, perimortem trauma is exacerbated by heat [59][60][61] whereby pre-existing fracture lines radiating from impact points extend further along the bone shaft and increase in depth. However, in these studies, existing fracture lines prior to burning were notably different from heat fractures [12,29] which were sharp, well-defined and the majority penetrating the cortex, particularly the longitudinal ones.…”
Section: Discussionmentioning
confidence: 99%
“…The results have shown that signatures associated with sharp and blunt force trauma were not entirely masked by heat exposure and that there is potential for future standardization of fracture analysis in burnt bone given further experimentation of this nature. In the literature, perimortem trauma is exacerbated by heat [59][60][61] whereby pre-existing fracture lines radiating from impact points extend further along the bone shaft and increase in depth. However, in these studies, existing fracture lines prior to burning were notably different from heat fractures [12,29] which were sharp, well-defined and the majority penetrating the cortex, particularly the longitudinal ones.…”
Section: Discussionmentioning
confidence: 99%
“…The same type of experimental setting has also been previously used to simulate the behavior of human bone through the use of the same type of samples. However, it is worth considering that the lack of interposition of soft tissues could be a confounding factor, and therefore a limitation of the present study .…”
Section: Discussionmentioning
confidence: 96%
“…Apart from one specimen impacted at 885 m/s that exhibited two macroscopic radial fractures, impacted porcine scapulae did not show the large radial or concentric fractures that are commonly associated with gunshot entry and exit sites in human crania. These fracture types are also typically absent in bovine scapulae subjected to ballistic impact [ 6 ] but have been documented in bovine ribs [ 56 ]. Radially and concentrically orientated cracks were identified around the cortical entry at the microscopic scale in both re-bound and perforating impacts, but whilst the radial cracks may be analogous to those seen macroscopically in human material the concentric cracks are not.…”
Section: Discussionmentioning
confidence: 99%